IMPLEMENTATION OF CHARACTER EDUCATION IN FORMING THE HOLISTIC PERSONALITY OF STUDENTS - Muhammad Kholilurrohman; Badrul Mudarris (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to examine the implementation of character education in the holistic personality development of Islamic boarding school students, encompassing intellectual, spiritual, moral, and social aspects. The main focus of the study is how character values are instilled in the Islamic boarding school environment as an effort to shape individuals with noble character and usefulness in society. The research method used is qualitative with a descriptive approach, through observation, in-depth interviews with caregivers, ustadz, and students, and documentation analysis. The results show that character education in Islamic boarding schools is implemented through the habituation of worship, teacher role models, discipline, social interaction, and the integration of Islamic values into learning activities and daily life. This implementation not only shapes individual morality but also develops emotional intelligence, independence, and social awareness in students. The implications of this study confirm that consistent and comprehensive character education can produce a generation of students with holistic personalities, ready to face global challenges without losing their Islamic identity. Furthermore, these findings can serve as a reference for other educational institutions in developing sustainable character development models.